GSNO Reductase and β(2) Adrenergic Receptor Gene-gene Interaction: Bronchodilator Responsiveness to Albuterol - Choudhry, Shweta (2010)
BACKGROUND: Short-acting inhaled β(2)-agonists such as albuterol are used for bronchodilation and are the mainstay of asthma treatment worldwide. There is significant variation in bronchodilator responsiveness to albuterol not only between individuals but also across racial/ethnic groups. The β(2)-adrenergic receptor (β(2)AR) is the target for β(2)-agonist drugs. The enzyme S-nitrosoglutathione reductase (GSNOR), which regulates levels of the endogenous bronchodilator S-nitrosoglutathione, has been shown to modulate the response to β(2)-agonists. OBJECTIVE: We hypothesized that there are pharmacogenetic interactions between GSNOR and β(2)AR gene variants which are associated with variable response to albuterol. METHODS: We performed family-based analyses to test for association between GSNOR gene variants and asthma and related phenotypes in 609 Puerto Rican and Mexican families with asthma. In addition, we tested these subjects for pharmacogenetic interaction between GSNOR and β(2)AR gene variants and responsiveness to albuterol using linear regression. Cell transfection experiments were performed to test the potential effect of the GSNOR gene variants. RESULTS: Among Puerto Ricans, several GSNOR SNPs and a haplotype in the 3′UTR were significantly associated with increased risk for asthma and lower bronchodilator responsiveness (p = 0.04 to 0.007). The GSNOR risk haplotype affects expression of GSNOR mRNA and protein, suggesting a gain of function. Furthermore, gene-gene interaction analysis provided evidence of pharmacogenetic interaction between GSNOR and β(2)AR gene variants and the response to albuterol in Puerto Rican (p = 0.03), Mexican (p = 0.15) and combined Puerto Rican and Mexican asthmatics (p = 0.003). Specifically, GSNOR+17059*β(2)AR+46 genotype combinations (TG+GG*AG and TG+GG*GG) were associated with lower bronchodilator response. CONCLUSION: Genotyping of GSNOR and β(2)AR genes may be a useful in identifying Latino subjects, who might benefit from adjuvant therapy for refractory asthma.